2017
DOI: 10.1111/vde.12413
|View full text |Cite
|
Sign up to set email alerts
|

Bartonellosis, One Health and all creatures great and small

Abstract: Background Bartonellosis is a zoonotic infectious disease of worldwide distribution, caused by an expanding number of recently discovered Bartonella spp. Objectives This review serves as an update on comparative medical aspects of this disease, including the epidemiology, pathogenesis, clinical diagnosis, treatment and challenges. Results Of comparative medical importance, Bartonella spp. are transmitted by several arthropod vectors, including fleas, keds, lice, sand flies, ticks and, potentially, mites and sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
125
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 118 publications
(130 citation statements)
references
References 81 publications
(362 reference statements)
2
125
0
3
Order By: Relevance
“…Although B. rochalimae is believed to infect rodents [2, 7], our phylogenetic analysis clearly showed that together with a Bartonella sequence obtained from a bank vole from France ([6]; a sequence that was very close to ours but not totally identical) our sequences formed a sister branch to B. rochalimae isolates from dogs/humans. Buffet et al [6] proposed a new species name for this genotype, “ Bartonella senartensis ”, but the full description of this species has not yet been completed.…”
Section: Discussionmentioning
confidence: 64%
See 4 more Smart Citations
“…Although B. rochalimae is believed to infect rodents [2, 7], our phylogenetic analysis clearly showed that together with a Bartonella sequence obtained from a bank vole from France ([6]; a sequence that was very close to ours but not totally identical) our sequences formed a sister branch to B. rochalimae isolates from dogs/humans. Buffet et al [6] proposed a new species name for this genotype, “ Bartonella senartensis ”, but the full description of this species has not yet been completed.…”
Section: Discussionmentioning
confidence: 64%
“…Infection may contribute to the development of an important vector-borne disease: bartonellosis [1, 2]. Of the 36 named and about 20 “ Candidatus ” species, 17 are recognized as causes of increasing numbers of human and animal bartonellosis cases [2].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations